PENGAWASAN DINAS KELAUTAN DAN PERIKANAN KABUPATEN INDRAGIRI HILIR DALAM USAHA PENANGKAPAN IKAN TAHUN 2012-2013 - Hendi Efriyansah; M.Y.Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Supervision is very important in all work, especially in government, lack ofsupervision is a phenomenon that is polemical and losses for various parties, thisphenomenon occurs in Indragiri Hilir, where the supervision of the Department of Marineand Fisheries to Enterprises Fishing less than the maximum because there are many fishingvessels who do not have license arrest but still fishing sepenggunaan toxins in the process ofcatching fish. The authors wanted to examine further on the Control of Marine and Fisheriesin Enterprise Fishing Year 2012-2013.The purpose of this study was to determine the mechanism of supervision conductedby the Department of Marine and Fisheries Indragiri Hilir through to the fishing effort anddetermine the barriers that lead to a lack of oversight conducted by the Department ofMarine and Fisheries Indragiri Hilir in monitoring fishing effort. The method used isdescriptive qualitative. Informants in this study is the Department of Marine and FisheriesIndragiri Hilir Environment Agency Indragiri Hilir and Fishermen. Data CollectionTechniques with interviews to determine the extent of Supervision Department of Marine andFisheries in the fishing business. Qualitative data analysis technique that is performed on thedata, in this case the qualitative data in the form of information associated with the dataother then to get clarity on the truth.Results from this study, Monitoring Department of Marine and Fisheries IndragiriHilir in Enterprise Fishing has been carried out and in accordance with existing regulations,just not running optimally, due to lack of infrastructure and lack of funds to conductsurveillance, then the next factor less accuracy officers at while supervising and less firmnesssanctions applied so as not to make the fishermen fear or deterrent.Keywords: Control , Marine and Fisheries Agency, Business